PENGARUH PENGGUNAAN AIR SUMUR , AIR COOLANT , AIR TETES AC TERHADAP SUHU MESIN PADA MOBIL TOYOTA KIJANG GRAND EXTRA 1994 - Budi Yono (LPPM Politeknik LP3I Medan, 2020)
Engine heat is generated from the combustion of fuel in the cylinder to generate power, but if left unchecked, it will cause an overheating effect. The engine temperature must be stabilized by the cooling system assisted by coolant through the radiator so that the engine working temperature can be maintained. There are several variations of the coolant used as the test medium (well water, AC drip water, coolant water that has different specifications from one another. This research was conducted on July 15, 2020 using the Toyota Grand Extra 1994 car. (coolant) used is water. Research Purposes Aim to determine the temperature of the engine produced by a car using a variation of liquid water The test is carried out at a distance of 3 km, 8 km, 11.5 km, 15 km. engine 640C, 770C, 810C, 85 0C. For liquid molasses it produces engine temperatures of 690C, 750C, 810C, 810C. For Coolant water liquid produces an engine temperature of 530C, 680C, 670C, 720C. Of the three liquids, the most effective is liquid. water coolant. Keywords: Well water, Sugarcane Drops, Coolant Water, Radiator, Coolant